Предмет: Алгебра,
автор: Helena19622may
x(x(x-1))+6=x(x+3)(x-4)
Ответы
Автор ответа:
0
x(x^2 - x) + 6 = x( x^2 - x - 12)
x^3 - x^2 + 6 = x^3 - x^2 - 12x
x^3 - x^3 - x^2 + x^2 + 12x = - 6
12x = - 6
x = - 6/12
x = - 0,5
x^3 - x^2 + 6 = x^3 - x^2 - 12x
x^3 - x^3 - x^2 + x^2 + 12x = - 6
12x = - 6
x = - 6/12
x = - 0,5
Похожие вопросы
Предмет: Физика,
автор: kfodndndkeo
Предмет: Математика,
автор: shadowficus1
Предмет: Русский язык,
автор: eldar3659
Предмет: Математика,
автор: STMSN
Предмет: Математика,
автор: STMSN